Effect of transport stress on apoptosis and autophagy in goat lung cells - Zhuo, Yu; Hu, Yunhai; Jin, Yangshan; Ye, Tian; Yang, Yanzhen; Liu, Ben; Zheng, Wenya; Ding, Songlin; Yang, Xue; Zheng, Lucheng; Hu, Wei; Fang, Manxin; et al. (Frontiers in Veterinary Science, 2025)
IntroductionRoad transportation exposes goats to thermal, mechanical, and microbial stressors that can compromise their welfare by triggering pulmonary apoptosis and autophagy processes associated with tissue damage and immunosuppression.MethodsTo explore potential biomarkers for transport-related welfare assessment, this study analyzed lung tissues from nine Ganxi goats (n = 9; 0 h control, 2 h/6 h transport groups) through an integrated experimental approach: TUNEL assays quantified apoptosis rates, immunohistochemistry mapped protein localization, Western blotting analyzed protein expression levels, and qPCR profiled gene expression of apoptotic regulators (Bax, Bcl-2) alongside autophagy-related markers (LC3B, p62, PINK1, Parkin).ResultsResults indicated time-dependent cellular stress patterns, where the 2 h group displayed elevated apoptosis rates, while the 6 h group exhibited upregulated Parkin expression (p < 0.05) and altered regulation of apoptotic [Bcl-2-associated X-protein (Bax)/B-cell lymphoma-2 (Bcl-2)] and autophagy-related genes (Microtubule-associated protein 1 light chain 3B (LC3B), p62, PTEN-induced putative kinase 1 (PINK1)/Parkin). Protein localization analyses revealed compartment-specific responses, with Bcl-2/Bax primarily in bronchial epithelia and LC3B/PINK1/Parkin in alveolar cells, suggesting spatially distinct stress adaptation mechanisms. Observed molecular changes coincided with histological evidence of pulmonary alterations, implying a potential interplay between apoptosis and autophagy in transport-induced cellular stress. The identification of time-sensitive molecular shifts (e.g., transient apoptosis elevation at 2 h, and progressive Parkin activation at 6 h) could inform hypotheses for monitoring transport-associated physiological responses.DiscussionThese findings highlight the need for further investigation into transport duration effects, with shorter intervals (e.g., ≤2 h) warranting evaluation for acute stress mitigation, and prolonged transport (e.g., >6 h) requiring characterization of cumulative autophagic impacts. The mechanistic insights can contribute to developing science-informed strategies for assessing transport stress, aligning animal welfare research with objectives to enhance sustainable livestock management practices.